Rapid urease test (RUT) for evaluation of urease activity in oral bacteria in vitro and in supragingival dental plaque ex vivo - Gunnar Dahlén; Haidar Hassan; Susanne Blomqvist; Anette Carlén (BMC, 2018)
Abstract Background Urease is an enzyme produced by plaque bacteria hydrolysing urea from saliva and gingival exudate into ammonia in order to regulate the pH in the dental biofilm. The aim of this study was to assess the urease activity among oral bacterial species by using the rapid urease test (RUT) in a micro-plate format and to examine whether this test could be used for measuring the urease activity in site-specific supragingival dental plaque samples ex vivo. Methods The RUT test is based on 2% urea in peptone broth solution and with phenol red at pH 6.0. Oral bacterial species were tested for their urease activity using 100 μl of RUT test solution in the well of a micro-plate to which a 1 μl amount of cells collected after growth on blood agar plates or in broth, were added. The color change was determined after 15, 30 min, and 1 and 2 h. The reaction was graded in a 4-graded scale (none, weak, medium, strong). Ex vivo evaluation of dental plaque urease activity was tested in supragingival 1 μl plaque samples collected from 4 interproximal sites of front teeth and molars in 18 adult volunteers. The color reaction was read after 1 h in room temperature and scored as in the in vitro test. Results The strongest activity was registered for Staphylococcus epidermidis, Helicobacter pylori, Campylobacter ureolyticus and some strains of Haemophilus parainfluenzae, while known ureolytic species such as Streptococcus salivarius and Actinomyces naeslundii showed a weaker, variable and strain-dependent activity. Temperature had minor influence on the RUT reaction. The interproximal supragingival dental plaque between the lower central incisors (site 31/41) showed significantly higher scores compared to between the upper central incisors (site 11/21), between the upper left first molar and second premolar (site 26/25) and between the lower right second premolar and molar (site 45/46). Conclusion The rapid urease test (RUT) in a micro-plate format can be used as a simple and rapid method to test urease activity in bacterial strains in vitro and as a chair-side method for testing urease activity in site-specific supragingival plaque samples ex vivo.